2015
DOI: 10.1007/s00726-015-2044-8
|View full text |Cite
|
Sign up to set email alerts
|

Ketimine reductase/CRYM catalyzes reductive alkylamination of α-keto acids, confirming its function as an imine reductase

Abstract: Recently, crystalized mouse ketimine reductase/CRYM complexed with NADPH was found to have pyruvate bound in its active site. We demonstrate that the enzyme binds α-keto acids, such as pyruvate, in solution, and catalyzes the formation of N-alkyl-amino acids from alkylamines and α-keto acids (via reduction of imine intermediates), but at concentrations of these compounds not expected to be encountered in vivo. These findings confirm that, mechanistically, ketimine reductase/CRYM acts as a classical imine reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Furthermore, CRYM expression is possibly upregulated through the activator protein-1 (AP-1) site in the promoter (37). Another important CRYM function has also been identified: When combined with ketimine reductase, it may act as a classical imine reductase (38). In addition, CRYM has a critical role and is regarded as a novel androgen-regulated gene whose expression is elevated in prostate cancer (39).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CRYM expression is possibly upregulated through the activator protein-1 (AP-1) site in the promoter (37). Another important CRYM function has also been identified: When combined with ketimine reductase, it may act as a classical imine reductase (38). In addition, CRYM has a critical role and is regarded as a novel androgen-regulated gene whose expression is elevated in prostate cancer (39).…”
Section: Discussionmentioning
confidence: 99%
“…Combining in vitro assays with the ALD1 and SARD4 homologs from H. serrata with use of deuterium‐labeled l ‐lysine indicated that SARD4 reduces the ketiminic C=N bond of 1,2‐DP rather than the C=C bond of the 2,3‐DP enamine (Xu et al ., ). This is in line with the reported reduction of ketimine substrates by mammalian CRYM (Hallen et al ., ). SARD4‐mediated reductive consumption of 1,2‐DP might shift the ketimine/enamine equilibrium towards the ketimine form and thus constantly reestablish reducible 1,2‐DP from the chemically more stable enamine 2,3‐DP.…”
Section: Catabolism Of L‐lysine To Pip and Conversion Of Pip To N‐hymentioning
confidence: 97%
“…or any other IRED homologs which have been reported [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] . The CpIM1 gene was identified using a human Mu crystallin (CRYM) gene sequence as a template, which is reportedly a ketimine reductase that catalyzes the alkylamination of various keto-acids [37] . CpIM1 showed a 24.5% identity with the human CRYM gene and belonged to the ornithine cyclodeaminase (OCD-Mu) family of proteins.…”
Section: Resultsmentioning
confidence: 99%